2018
DOI: 10.3390/nu10121991
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus paracasei KW3110 Prevents Blue Light-Induced Inflammation and Degeneration in the Retina

Abstract: Age-related macular degeneration and retinitis pigmentosa are leading causes of blindness and share a pathological feature, which is photoreceptor degeneration. To date, the lack of a potential treatment to prevent such diseases has raised great concern. Photoreceptor degeneration can be accelerated by excessive light exposure via an inflammatory response; therefore, anti-inflammatory agents would be candidates to prevent the progress of photoreceptor degeneration. We previously reported that a lactic acid bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 43 publications
2
31
0
1
Order By: Relevance
“…In addition, IL-10 production was upregulated in the supernatant from KW3110-stimulated human monocytes ( Fig 6A), and both KW3110 and recombinant IL-10 protein treatments suppressed IL-1β production in LPS/ATP-stimulated cells (Fig 6B). IL-10 is a representative anti-inflammatory cytokine and is reported to be involved in inhibition of IL-1β production [23][24][25], which is consistent with our results shown in Fig 2B. KW3110 was previously reported to activate macrophages by interacting with gut immune cells and promoting cytokine production, including IL-10 [10,13,20]. It has also been reported that KW3110 suppresses the level of pro-inflammatory cytokines such as IL-1β in the serum of aged mice or the retina of blue-light exposure-induced mice [13,14].…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, IL-10 production was upregulated in the supernatant from KW3110-stimulated human monocytes ( Fig 6A), and both KW3110 and recombinant IL-10 protein treatments suppressed IL-1β production in LPS/ATP-stimulated cells (Fig 6B). IL-10 is a representative anti-inflammatory cytokine and is reported to be involved in inhibition of IL-1β production [23][24][25], which is consistent with our results shown in Fig 2B. KW3110 was previously reported to activate macrophages by interacting with gut immune cells and promoting cytokine production, including IL-10 [10,13,20]. It has also been reported that KW3110 suppresses the level of pro-inflammatory cytokines such as IL-1β in the serum of aged mice or the retina of blue-light exposure-induced mice [13,14].…”
Section: Plos Onesupporting
confidence: 90%
“…The supernatant transferal experiment ( Fig 1B) suggested that molecules released from KW3110-treated J774A.1 cells suppressed IL-1β production in LPS/ATP-stimulated cells. KW3110 induces IL-10 production in M2 macrophages; therefore, we hypothesized that KW3110 suppresses the inflammatory response in macrophages through IL-10 induction [13,20]. KW3110 treatment dose-dependently increased IL-10 levels in J774A.1 cell supernatant (1.25 μg/mL, P = 0.002; 2.5 μg/mL, P < 0.001; 5 μg/mL, P < 0.001; Fig 2A).…”
Section: Kw3110 Treatment Suppresses Il-1β Production In Lps/atp-stimmentioning
confidence: 96%
“…Therefore, a clear link has been shown to exist between IBD and the vaginal flora that contribute to the early development of the intestinal microbiota, which is dominated by Lactobacillus spp. One such species, Lactobacillus paracasei, has shown particular promise as a probiotic candidate through its ability to decrease the secretion of pro-inflammatory cytokines, increase the production of anti-inflammatory cytokines 6 , increase immunomodulatory control 7,8 , and decrease IBD symptom severity 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics (also called psychobiotics or bio-friendly agents), defined "as a source of live (viable) naturally occurring microorganisms (direct-fed microbials, DFMs)", have been used as dietary supplements to target gut microbiota (microbiome) for a novel promising therapeutic approach of various diseases including social stressinduced mental disorders in humans and various experimental animals [27][28][29][30][31][32][33][34][35][36]. Different probiotic strains, for example, have been investigated as functional food or therapeutic treatment of various diseases, including Bifidobacterium bifidum [37][38][39]; Bifidobacterium bifidum (BGN4) and Bifidobacterium longum (BORI) [40,41]; Bifidobacterium pseudocatenulatum [42]; Lactobacillus helveticus [31,32]; Lactobacillus plantarum [43]; Lactobacillus paracasei (KW3110, [44]); Lactobacillus rhamnosus [45]; and Clostridium butyricum [46]. The results collected from these studies indicate that the effects of probiotics on physiological homeostasis, immunity, stress resistance, and related health status are affected by multiple factors, including the probiotic species, its concentration, and duration as well as the host's age and health status [47,48].…”
Section: Introductionmentioning
confidence: 99%